Hubungan kadar adiponektin dengan migren dan tension type headache - Eva Meutia; Alfansuri Kadri; Khairul P. Surbakti; Hasan Sjahrir (Fakultas Kedokteran USU, 2012)
Background: Migraine and tension type headache (TTH) are the primary headaches that most complained and can lead to disability significantly. Obesity is already known to be one of the headache chronification risk factors, and adiponectin is a cytokine that is secreted by adipocytes tissue primarily. Adiponectin has been known to play a role in modulated some inflammatory pathways of the primary headache pathophysiology or in central sensitization process in conjunction with chronic headache. Objective: To evaluate association level of adiponectin with migraine and TTH.Methods: This cross-sectional study was conducted in migraine and TTH patients who came to sefalgia outpatient department of Adam Malik Hospital, which sex-and age matched for this study sample. Each subject completed a questionnaire adapted from the research Ho KH and BK Ong-C, and do anthropometric examination also adiponectin examination at Prodia laboratory. Result: There is significantly difference of mean adiponectin level between migraine 7.58 (SD 4.69) and TTH 4.99 (SD 2.63) (P = 0.008). Association of adiponectin level with episodic migraine is found not significant (P = 0.35), but the significant association is found with TTH (P = 0.013), which adiponectin level is found higher in chronic TTH 8.5 (SD 1.39) than episodic TTH 4.64 (SD 2.47). From the Spearman correlation test, there is negative association between WHR with adiponectin level significantly (r = -0.28. P = 0.02).Conclusion: There is association between adiponectin level with TTH, but it’s not significant with episodic migraine, and there is negative association between WHR and adiponectin level.Keywords : migraine; tension type headache; adiponectin level; obesity; waist hip ratio